Characterisation of high fat, high sugar diet-induced epigenetic changes in skeletal muscle of wistar rats and metabolic effects of an aspalathin-rich rooibos extract - Myataza, Asive (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.